2021
DOI: 10.1016/j.cell.2021.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Secreted gelsolin inhibits DNGR-1-dependent cross-presentation and cancer immunity

Abstract: Highlights d Secreted gelsolin (sGSN) inhibits DNGR-1 binding to F-actin d sGSN dampens DNGR-1-dependent cross-presentation of dead cell-associated antigens d sGSN impairs DNGR-1-dependent cDC1-mediated antitumor immunity d Low sGSN expression and mutations in FABPs correlate with cancer patient survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 72 publications
1
65
0
Order By: Relevance
“…As a result, data mining identified a subset of those proteins that are associated with the tumor immune responses ( Figure 2A ). Of those proteins, we focused our attention on different proteins, such as gelsolin ( Giampazolias et al, 2021 ), periostin ( Zhou et al, 2015 ; Huizer et al, 2020 ) and osteopontin ( Wei et al, 2019 ; Li et al, 2021 ), which were exclusively detected in the secretome of WT PC + GB, and not in the other conditions. As these proteins might be good markers for GB prognosis dependent on GB-induced CMA in immunosuppressive PC ( Valdor et al, 2019 ), we experimentally confirmed the presence of these proteins and their mouse origin in the secretome of GB-conditioned PC.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, data mining identified a subset of those proteins that are associated with the tumor immune responses ( Figure 2A ). Of those proteins, we focused our attention on different proteins, such as gelsolin ( Giampazolias et al, 2021 ), periostin ( Zhou et al, 2015 ; Huizer et al, 2020 ) and osteopontin ( Wei et al, 2019 ; Li et al, 2021 ), which were exclusively detected in the secretome of WT PC + GB, and not in the other conditions. As these proteins might be good markers for GB prognosis dependent on GB-induced CMA in immunosuppressive PC ( Valdor et al, 2019 ), we experimentally confirmed the presence of these proteins and their mouse origin in the secretome of GB-conditioned PC.…”
Section: Resultsmentioning
confidence: 99%
“…Gelsolin, an abundant actin-depolymerizing plasma protein ( 33 ) decreases binding of F-actin to Clec9a in an in vitro system ( 47 ). In an in vivo cancer model, secreted gelsolin inhibits Clec9a-dependent cross presentation of antigen and dampens CD8+ T cell responses ( 48 ). In this study, we examined the role of gelsolin in neonatal hyperoxia-induced Clec9a+CD103+DC-mediated lung pro-inflammatory responses to RV infection and hypoalveolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Gelsolin depolymerizes F-actin decreasing its binding to Clec9a in an in vitro system ( 47 ). Secreted gelsolin inhibits Clec9a-dependent cross presentation of antigen and dampens CD8+ T cell responses in a cancer model in mice ( 48 ). However, the role of gelsolin in neonatal hyperoxia-induced, Clec9a+CD103+DC-mediated lung pro-inflammatory responses has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Among various DC subsets, cDC1s (XCR1+, CD103+) play a critical role in antitumour immunity. CLEC9A, (also known as DNGR1) is highly expressed on cDC1s and binds necrotic cell debris and promotes antigen processing in tumours (159)(160)(161). One of the reasons for checkpoint blockade failure is poor antigen presentation due to absence of co-stimulatory molecules and therefore modulation of DC function could increase responses to these therapies.…”
Section: Leveraging DC Biology In Cancer Therapiesmentioning
confidence: 99%